Key insights and perspectives from the Food Systems Summit Dialogues and the CAADP 3rd Biennial review process - Gosling, Amanda; Chesterman, Sabrina; Mutamba, Manyewu (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
This report forms part of an AICCRA knowledge series on Food Systems, providing key insights and perspectives from the Food Systems Summit Dialogues and the CAADP 3rd Biennial review process.